(untitled) (Research, Society and Development, 2021)
The diversity microbial in ethanolic fermentation generate different behavior metabolic that depended on the microorganisms present. Some kinetic parameters can tell how interactions between microorganisms are occurring in fermentation and can also predict your metabolic behaviors. However, there are little studys about the influence of interactions microbial on kinetic parameters in fermentation sugar cane. Therefore, this work aimed to understand the influence of the yeast strain Saccharomyces cerevisiae CAT-1, MONA, PE-2 and ATCC in the production of biomass, ethanol, glycerol and sugar consumption, as well as to evaluate the kinetic parameters by means of response surface methodology for mixing. From the biomass models generated, it was observed that the yeasts ATCC and MONA when in the presence of CAT-1 and PE-2 showed antagonisms. For the ethanol, the synergistic effect was verified for the mixture MONA/ATCC and CAT-1/PE-2 being that CAT-1 and PE-2 were the yeasts that strongly favored the ethanol production. It stands out yeast MONA due to having lower glycerol production, character desirable in the sugar and alcohol industry. Thus, it is clear that from the analysis employed it was possible to infer about the kinetic behavior of the yeasts in pure cultures as well as the effect of the interaction between them during the cultivation.